New approach in modelling of the patients behavior in Primary Health Care (PHC) (Automatyka/Automatics, 2017)
The purpose of this paper is to show the concept of simulation of Primary Health Care (PHC) patients behavior. There are two reasons for interest in this area. The first of them is the need for support in decision making regarding financing and management of PHC facilities on levels from national (Natonal Health Fund) to local (PHC provider). The second one is the lack of effective methods for such population modeling. In this paper author describe an idea of probability distribution modeling and present preliminary results of patient visits simulation over a period of a year.Celem artykułu jest pokazanie koncepcji symulacji zachowań pacjentów Podstawowej Opieki Zdrowotnej (POZ). Temat ten jest ważny z dwóch powodów. Po pierwsze model taki mógłby posłużyć w podejmowaniu decyzji w rozdzielaniu funduszy pomiędzy jednostkami POZ przez Narodowy Fundusz Zdrowia. Drugim z powodów jest obecnie brak efektywnych metod modelowania populacji POZ. W niniejszej pracy autor opisuje ideę modelowania populacji przy użyciu rozkładu prawdopodobieństwa i przedstawia wstępne wyniki symulacji dla wizyt pacjentów w ciągu roku.